RESPON TANAMAN KEDELAI (Glycine max L. Merril) TERHADAP TINGGI MUKA AIR TANAH DAN PEMBERIAN DOSIS PUPUK MAJEMUK DI MEDIA GAMBUT - Ulfa Dwi Anggraini; Islan Islan; Syafrinal Syafrinal (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aims to determine the response of soybean crops to soil water level and dosing of compound fertilizer in peat media. Performed from January to April 2017. This study used Completely Randomized Design (RAL) which consists of 2 factors. The first factor is the groundwater level (T) 15 cm below the soil surface, 20 cm below the soil surface and 25 cm below the soil surface. The second factor is dosing of compound fertilizer (A) 200 kg/ha, 250 kg/ha and 300 kg/ha. The parameters observed were plant height, percentage of pods, root dry weight per plant, dry weight of crop per plant, plant age start flowering, number of primary branch, percentage of pods, dry seed weight per plant and 100 seed weight. The data obtained were analyzed statistically with vocabulary and continued with Duncan's New Multiple Range Test (DNMRT) at 5%. The results showed that the high water level of 25 cm and the dosage of 300kg/ha compound gave the best result on the parameters of plant height, the age of the flowering plants, the dry weight of the roots per plant, the dry weight of crop per plant and the weight of dry seed per plant. Keywords: Soybean, Water table height, Compound Fertilizer, Peatland